Communication - internal and external linkages. - Ahmad, Abdul Manap (1976)
The paper discusses communication in Agricultural Research and agricultural research management. The importance of agricultural research and the role of communication in agricultural research is elaborated. Reference is also made to what constitutes communication and the communication process; and the essential elements of the process are discussed. As the process of communication affects so many sectors and factors, the linkages necessary to affect proper communication between factors and sectors are discussed. The assumptions made to institute proper communication at the various points are highlighted briefly. Besides, the classification, the channels and the problems of linkages in communication are elaborated. A brief outline of the strategies to be employed to have effective communication in agricultural research is also made. Agricultural research has its main objective the application of a wide variety of scientific disciplines to the development of new approaches to agricultural production, and to the problems faced by the farmers. Communication and its related components, playing a major role in Agricultural Research, is defined as the process by which the knowledge or idea is transferred from a source (production centre) to a receiver with the intent of instituting a change in his behaviour, attitude and other values. The purpose of communication is to bring about certain desired effects on the part of the receiver.